PENGARUH FAKTOR KOMUNIKASI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DENGAN KOMPENSASI SEBAGAI MODERATING - Widodo, Joko -; -, Sunarso - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2010)
AbstraCT The purpose of this study were: (1) analyze the significance of the influence of communication on the performance of employees, (2) analyze the significance of the influence of leadership on employee performance, (3) analyze the effect of moderating effects of compensation on communication, and leadership performance. The population in this study is the Public Works Department Water Affairs and Energy and Mineral Resources Karanganyar. The total population by 55 people. Given the relatively small population of the entire population were subjected to experiments or census. Based on the results of the t test, the communication variables significantly affect the performance of the Employee Fields Mineral Water and Energy Resources Department of Public Works Karanganyar. While the leadership variables do not significantly affect the performance of the Employee Field Mineral Water and Energy Resources Department of Public Works Karanganyar. By testing the absolute difference (absolute difference regression analysis 1) the results obtained compensation not moderate the influence of communication on employee performance. Test of absolute difference (absolute difference regression 2) results obtained compensation not moderate the influence of leadership on employee performance Field Mineral Water and Energy Resources Department of Public Works Karanganyar. Keywords: communication, leadership, compensation, performance